Prevalence of Novel Psychoactive Substance (NPS) Use in Patients Admitted to Drug Detoxification Treatment - Specka, Michael; Kuhlmann, Thomas; Sawazki, Jürgen; Bonnet, Udo; Steinert, Renate; Cybulska-Rycicki, Monika; Eich, Helmut; Zeiske, Benita; Niedersteberg, Antje; Schaaf, Luzia; Scherbaum, Norbert (Frontiers in Psychiatry, 2020)
Background: About 15 years ago, a diverse group of new recreational psychotropic substances began to emerge, which were marketed for example as “legal highs”, “research chemicals” or “designer drugs”. These substances were later subsumed under the label “Novel Psychoactive Substances” (NPS). Important NPS classes are cathinones, synthetic cannabimimetics, phenethylamines, and herbal drugs. The health care system for psychotropic substance use disorders (SUDs) traditionally focused on a few substances, such as alcohol, heroin, cocaine, amphetamines, or cannabis. Users of illicit substances often engage in polydrug use. However little is known about the prevalence of NPS use within the group of “classical” illicit substance users. Objective: We investigated lifetime and recent use of NPS and other drugs in patients who underwent in-patient detoxification treatment from illicit drugs in Germany. Methods: In a multicenter study with 8 participating facilities, patients admitted to treatment underwent a standardized interview at admission, concerning their past and current substance use. The interview comprised classical substances of abuse, NPS, and rarely used substances such as LSD. In addition, participating sites had the opportunity to analyse their patients’ routine drug screenings by means of gas chromatography/mass spectrometry (GC/MS), which permitted detection of NPS. Results: Interviews from 295 patients could be analyzed. Most patients were opiate dependent and multiple substance users. About 32% reported use of synthetic cannabimimetics during lifetime, but ususally only a few times. An important reason for their use was that NPS were not detected by drug testing in prisons or drug treatment facilities. Cathinones, herbal drugs or other NPS had rarely been used during lifetime. NPS use during the last 30 days before admission was nearly zero. This was confirmed by urine analysis results. In contrast, lifetime and current use of opiates, alcohol, cocaine, benzodiazepines, and cannabis was high. In addition, 18% reported of regular unprescribed pregabalin use during lifetime, and 20% had recently used pregabalin. Conclusion: Patients admitted to drug detoxification treatment showed multiple substance use, but this did not include NPS use. The diversion of legal medications such as pregabalin in this group is a serious concern.